(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article discusses ways to increase cognitive interest in mathematics among younger schoolchildren, which has not lost its relevance to this day. The success of learning depends on the quality of assimilation of knowledge by students, on how interested the child is in this subject.